PENGARUH EFEK ENTRENCHMENT, ALIGMENT DAN DEWAN KOMISARIS INDEPENDEN TERHADAP VOLUNTARY DISCLOSURE PADA PERUSAHAAN OTOMOTIF YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Sri Mulyati; Rauzatul Jannah (Department of Accounting, Faculty of Economics & Business, 2019)
This study aims to know the Effect of Entrenchment Effects, Alignment and Independent Board of Commissioners toward Voluntary Disclosure of Automotive Companies Listed on the Indonesia Stock Exchange during 2014-2017. The data used in this study are secondary data as many as 12 samples with 48 observations. The sampling technique used is purposive sampling technique. The method used to analyze the relationship between the independent variables and the dependent variable is the multiple linear regression method and the classical assumption test. The results showed that the entrenchment and alignment partially has a negative and significant effect on Voluntary Disclosure of Automotive Companies listed on the Indonesia Stock Exchange, while independent commissioners have a positive and significant effect on Voluntary Disclosure of Automotive Companies listed on the Indonesia Stock Exchange. Simultaneously, the entrenchment, alignment and independent board of commissioners have a positive and significant effect on Voluntary Disclosure of Automotive Companies listed on the Indonesia Stock Exchange.